USULAN A. MACINTYRE KEMBALI KE ETIKA KEUTAMAAN:: SEBUAH SOLUSI ATAU NOSTALGIA BELAKA? - J. Sudarminta (Kanz Philosophia: A Journal for Islamic Philosophy and Mysticism, 2014)
As an alternative to the impasse of the modern-enlightenment project in ethics, Alasdair MacIntyre suggests to recourse to virtue-ethics. This article will present first, what MacIntyre means by the modern-enlightenment project in ethics, secondly, his critique of that project, especially his arguments why such ethics is bound to fail. Thirdly, why, according to him, developing virtue-ethics, somewhat like the Aristotelian-Thomistic model, will provide a solution to the impasse. Finally, I would like to make a short evaluation of MacIntyre’s suggestion by focusing on the question whether his suggestion to recourse to virtue-ethics is just a nostalgia to the past as criticized by Ross Poole. I will argue in this article that, despite MacIntyre’s failure to give concrete examples of good modern ethical communities that live out his model of virtue-ethics, as Poole has rightly pointed out, as long as human being can still agree on certain basic human values upon which global ethics of virtue can be built, MacIntyre’s suggestion is not simply a nostalgic recourse to the past as Ross Poole believes. MacIntyre’s recourse to virtue-ethics can indeed provide solution to overcome the danger of moral nihilism looming over the modern-enlightenment project and it can also provide reasonable ground for living ethically.